Enantioselective Resolution Copolymerization of Racemic 2, 3‐Disubstituted cis‐Epoxides with CO2 Mediated by Binuclear Cobalt(III) Catalyst†. Issue 9 (3rd July 2021) - Liu, Yan‐Lan; He, Guang‐Hui; Liu, Ye; Lu, Xiao‐Bing
Main observation and conclusion: Enantioselective resolution copolymerization of racemic internal epoxides with carbon dioxide (CO2 ) is a challenging issue because of their poor reactivity and complicated regio/stereoselectivity. Herein, we describe the first enantioselective resolution copolymerization of racemic aromatic 2, 3‐disubstituted cis ‐epoxides and CO2 using enantiopure dinuclear cobalt(III) complexes as catalyst under mild conditions, affording the corresponding polycarbonates with completely alternating structure and good enantioselectivity in the range of 70% to 97% ee . The isotactic polycarbonate from β ‐methylstyrene oxide is a typical semicrystalline material, possessing a melting point of 241 o C; while other isotactic‐enriched copolymers from 2, 3‐disubstituted cis ‐epoxides bearing a substitute group on the aromatic ring are amorphous, having glass transition temperatures between 86 o C and 124 o C. Interestingly, the copolymer selectivity is correlated well with the Hammett substituent constant, and the highest polymer selectivity of 98% was found in the system using the epoxides bearing an electron‐donating group on the benzene ring. Abstract :